2021
DOI: 10.3991/ijet.v16i02.18819
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of E-Portfolio in Higher Education

Abstract: The e-portfolio development and introduction are based on the fact that the reflective practice of its creation allows students to document and track learning, develop a coherent picture of experience, and improve self-understanding. The study took place at Lomonosov Moscow State University (Russia); an assessment tool to design and develop electronic portfolios in the higher education system has been developed and tested in the study. A survey focused on the value of an electronic portfolio, which was positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 34 publications
1
22
0
1
Order By: Relevance
“…e outcomes supported the findings in [52] and of Belanoff and [53], as cited in [7,8,50,[54][55][56][57][58][59][60].…”
Section: Results Of the First Research Questionsupporting
confidence: 87%
See 2 more Smart Citations
“…e outcomes supported the findings in [52] and of Belanoff and [53], as cited in [7,8,50,[54][55][56][57][58][59][60].…”
Section: Results Of the First Research Questionsupporting
confidence: 87%
“…e constructivist approach is presented on the basis of portfolio studies because the student needs construction in his/her mind for each study and activity to be placed in the portfolio [8]. He/she reflects his/her learning to his/her studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once all the steps have been inputted into Miro, the students can have an in-depth look into their design process and how it evolved over time (see Figure 4). This so-called visual journal in Miro supported the development of students' self-assessment, reflection and action planning skills [37][38][39].…”
Section: Resultsmentioning
confidence: 99%
“…Eleven indicators were used to measure motivation as followed: autonomy, confidence, eagerness to learn, high performance, independence, enjoyment, self-efficacy, sense of achievement, sense of belonging, sense of engagement, and sympathy. Moreover, Syzdykova, Koblandin, Mikhaylova, and Akinina (2021) found that the assessment of the E-portfolio was suitable for higher education and integrated learning. Students could create their E-portfolio, manage the working documents, catch up with their learning progress, illustrate related learning concepts.…”
Section: The Pre-service Teachers Have Positive Opinions Toward This Conduct At the Overall Excellent Levelmentioning
confidence: 99%